The Materiality of Faith: Divine Belief Manifested in Historical and Material Reality A Study of the Material Forms of Spiritual Expression in Light of the Holy Quran and Islamic History (Journal of the College of Basic Education, 2026)
This study proceeds from the foundational Islamic principle that faith (Iman) is divine revelation bestowed by Allah upon His servants as guidance and light. It is not derived from material conditions or socio-economic accumulations; rather, it is a divine gift embedded by Allah in the hearts of believers. The central contribution of this research, however, lies in examining how this divinely-sourced faith manifests and expresses itself through tangible, material, and historical forms — transforming rituals, institutions, and architectural monuments into civilizational expressions of a belief firmly rooted in the heart. This study therefore investigates the material forms through which divine faith becomes visible in Islamic history, while affirming unequivocally that the true source of creed is divine revelation as embodied in the Holy Quran and the Prophetic Sunnah. The research adopts the historical-analytical method in examining Islamic civilizational models — mosques, endowments (Waqf), madrasas, and reform movements — as material evidence of faith's power in building civilization.